EVALUATION OF THE INFLUENCE OF LOCAL HYDRAULIC RESISTANCE ON THE ENERGY CONSUMPTION OF PLASTIC GAS NETWORKS - Дорошенко, Юлія Іванівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Dissertation is devoted to evaluating the impact of local resistance on the hydraulic energy consumption of plastic gas networks. Studied and analyzed the practice of design of gas networks. Theoretical and experimental studies of the dynamics of the gas connections of plastic pipe thermistors and their coefficients of local resistance. A coefficients of equivalent length, depending on the type and number of local resistance on the length of 1 km of gas networks. The recommendations to improve the calculation of the gas network of polyethylene pipes, improving the design thermistor connections and the efficiency of their application. Analytical models dissertation is devoted to evaluating the impact of local hydraulic resistance on the energy consumption of plastic gas networks. Studied and analyzed the practice of design of gas networks. Theoretical and experimental studies of the dynamics of the gas connections of plastic pipe thermistors and their coefficients of local resistance. A coefficients of equivalent length, depending on the type and number of local resistance on the length of 1 km of gas networks.